"Petites Bonnes" minors sex trafficked in Morocco and Spain. (January 2021) - Melgar, Patricia; Merodio, Guiomar; Duque, Elena; Ramis-Salas, Mimar
Highlights: There are Moroccan girls (petites bonnes) who are vulnerable to sex trafficking. The presence of petites bonnes in Spain has not been analyzed. Child domestic work overlaps with labor and sexual abuse. Recommendations for developing primary prevention measures are offered. Abstract: The information currently available about girls and women who are trafficked worldwide for the purpose of sexual exploitation only shows us one part of the picture. In the Puigvert (2012–2014) TRATA: Life trajectories that move away or bring closer to the trafficking processes of sexual exploitation, through 25 qualitative techniques conducted with social service providers with a communicative orientation, we have identified a group of Moroccan adolescent girls between 12 and 18 years old who are particularly vulnerable to sex trafficking: the petites bonnes or young housemaids. Sexual exploitation, as well as sexual abuse that sometimes leads to pregnancy, can result in the flight or expulsion of these girls from their homes. These results unveil two recruitment elements that are used by trafficking networks: the irregular situation in which girls have arrived in a city and the circumstances of inequality in which they find themselves, including having low education levels and poor work experience. Furthermore, these elements make these girls invisible to the authorities and other professionals who could assist them. Based on these results, we conclude that tackling these challenges requires primary prevention measures that will increase the financial viability of the social groups at risk, establish programs that ensure successful educational trajectories for girls in their places of origin, and raise the awareness of people about this reality in their environments.